A3.26 Identifying T-Follicular-Helper-Like Cell Involvement in the Organization of Tubulointerstitial Inflammation in Human Lupus Nephritis and Renal Allograft Rejection. (25th February 2013) - Liarski, V; Brandt, D; Kaverina, N; Henderson, S; Chang, A; Utset, T; Labno, C; Peng, Y; Jiang, Y; Giger, M; Clark, M
Abstract : Background: Tubulointerstitial inflammation (TII) is a usual feature of lupus nephritis (LuN) and the infiltrate is organised into well-circumscribed T:B-cell aggregates or germinal centre-like structures. Materials and Methods: We analysed 42 LuN biopsies using confocal laser scanning microscopy (CLSM) for the qualitative presence of TFH -like CD4 + ICOS + cells (TIH )(n = 19 for ICOS-positive cases) and compared this with T-cell-mediated (TCM, n = 8) and mixed renal allograft (mixed RT, n = 7) rejection cases. Cellular make-up and relationships within TII were examined using CLSM to identify and compare the locations of TIH cells and CD20 + B cells by means of a computerised cell-distance algorithm. Results: The prevalence of TIH cells was found to be 45.2% in LuN, 64.2% in TCM, and 50% in mixed RT cases. Presence of these cells in LuN was statistically correlated with a worse grade of TII as scored by a blinded pathologist (2.05 versus 1.48, p = 0.04). ICOS-positive biopsies were associated with a higher mean serum creatinine in adult patients at time of biopsy (2.3 versus 1.1 mg/dL, p = 0.03) as well as GFR as measured by the MDRD equation and adjusted for patient sex (44.8 versus 74.1 mL/min/1.73 m 2, p = 0.04) with no statistical differences in age, sex, ISN/RPS LuN class, or NIH activity or chronicity indices. Cellular distance mapping revealed that TIH cells were spatially related to CD20 + B cells across LuN (42.9% of cells within 0.27 microns, n = 10 biopsies), control tonsil tissue (65.3%, n = 2 biopsies), and mixed RT cases (70.3%, n = 7 biopsies) as compared to other T cells (less than 20% for all groups, respectively). These associations remained unchanged after correction for total cellular density and T:B cell ratios. Low-density TCM cases showed a comparatively low rate of TIH :B cell association (15.0%, n = 8 biopsies) and these results were statistically significant (p < 0.0001 versus mixed RT and tonsil cases, p = 0.002 versus LuN). Comparing the above results against a theoretical model of random TIH :B-cell distribution revealed that the likelihood of our observations in LuN being due to chance was approximately 8.12 × 10 –41 . Conclusions: Our data reveal that TIH cells are present in similar rates across cases of renal allograft rejection as well as LuN. Their presence is associated with a higher degree of TII as well as worse renal function at time of biopsy in LuN. TIH cells are more likely to form proximal conjugates with naïve and activated B cells in tissues of diseases associated with aberrant autoantibody production (SLE, mixed RT) but not in processes where autoantibodies are absent (TCM).